Flow dynamics and magnetic induction in the von-Kármán plasma experiment. (10th October 2014) - Plihon, N.; Bousselin, G.; Palermo, F.; Morales, J.; Bos, W. J. T.; Godeferd, F.; Bourgoin, M.; Pinton, J.-F.; Moulin, M.; Aanesland, A.
Abstract : The von-Kármán plasma experiment is a novel versatile experimental device designed to explore the dynamics of basic magnetic induction processes and the dynamics of flows driven in weakly magnetized plasmas. A high-density plasma column (10 16 –10 19 particles. m −3 ) is created by two radio-frequency plasma sources located at each end of a 1 m long linear device. Flows are driven through J ×B azimuthal torques created from independently controlled emissive cathodes. The device has been designed such that magnetic induction processes and turbulent plasma dynamics can be studied from a variety of time-averaged axisymmetric flows in a cylinder. MHD simulations implementing volume-penalization support the experimental development to design the most efficient flow-driving schemes and understand the flow dynamics. Preliminary experimental results show that a rotating motion of up to nearly 1 km/s is controlled by the J ×B azimuthal torque.